Associations between trauma during adolescence and sense of purpose in middle-to-late adulthood. (September 2020) - Pfund, Gabrielle N.; Edmonds, Grant W.; Hill, Patrick L.
Early adverse experiences can hold lasting influence on later life outcomes, particularly during formative developmental periods such as adolescence. The current study evaluates the impact of different kinds of adolescent trauma on later sense of purpose in adulthood, using data from the Hawaii Longitudinal Study of Personality and Health. Participants ( n = 545) retrospectively reported three kinds of trauma during adolescence: (1) non-betrayal trauma, such as a natural disaster; (2) low betrayal trauma, such as being abused by a stranger; and (3) high betrayal trauma, such as being abused by a relative. At a later assessment, participants ( M age = 60.15, SD = 1.96) reported their sense of purpose. Trauma scores were uncorrelated with sense of purpose for the overall sample. However, the associations differed when comparing two of the largest cultural groups in the sample, Japanese Americans and Native Hawaiians. For participants who identified as Japanese American, trauma scores held a negative association with later sense of purpose across multiple measures. Results are discussed with respect to how early life experiences differentially impact purpose development across individuals.